Utilization of Yam Extract as an Alternative to Crystal Violet for Staining Streptococcus mutans Bacteria - Ridwan, Asriyani; Fatimah; Mutmainnah, Nurul; Faisal (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Gram staining is a fundamental technique in microbiology, vital for the initial identification of bacteria based on differences in cell wall structure, classifying them as Gram-positive and Gram-negative. This method is crucial for rapid clinical diagnosis. Currently, its primary stain, Crystal Violet, raises serious concerns due to its mutagenic, toxic, and environmentally unfriendly properties, necessitating the search for safer and more sustainable alternatives. This study focuses on the potential of yam tubers (Dioscorea sp.), an abundant local resource, as a substitute for Crystal Violet. Yam tubers are rich in anthocyanins, natural pigments with cationic properties and antibacterial activity, making them a promising dye candidate. The selected test bacterium was Streptococcus mutans, a Gram-positive, coccus-shaped bacterium and a major cause of dental caries, ideal for validating the staining ability of thick cell walls. The aim of this study was to evaluate the effectiveness of yam tuber extract in staining S. mutans and to compare its staining quality with standard Crystal Violet. The expected outcome is the creation of an economical, environmentally friendly, and sustainable staining method.